Structural features of paravertebral muscles in normal condition and degenerative diseases of the lumbar spine (literature review) - Radchenko, Volodymyr; Dedukh, Ninel; Ashukina, Nataliya; Skidanov, Artem (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Based on the analysis of scientific literature authors summarized information about the structural organization of the paravertebral muscles in normal condition and degenerative diseases of the lumbar spine. It is proved that in the paravertebral muscles originating from the dorsal myotomes (m. multifidus, m. erector spinae) unlike other skeletal muscles type I fibers dominate corresponding to function of maintenance of physiological posture they perform. Wherein the percentage of type I fibers in women is much higher than men stipulating their higher adaptive capacities and less fatigue. Moreover, unlike skeletal muscles of the extremities in m. multifidus type II fibers are much thinner than type I fibers. In patients with chronic back pain of various etiologies in paravertebral muscles during histological examination myogenic and neurogenic changes revealed manifesting by sarkopenia or just local disturbances. However, results regarding the distribution of fiber types I and II obtained are ambiguous which requires further study. Results of in-depth histochemical studies which will correspond to different subtypes of muscle fiber types I and II, the state in which of actin and myosin make it possible to expand the understanding of the structural and functional disorders of the muscles in patients with chronic back pain. Recently, much attention is paid to systemic changes in muscle tissue (sarkopenia) that accompany most diseases of musculoskeletal system. A detailed study of the structural and functional organization of the paravertebral muscles opens new perspectives for prevention of spine disorders in early and distant postoperative periods.